(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper aims to estimate the logarithmic coefficients for the class of functions with bounded turning. Hence, the upper bounds of the second-order for three types of determinants (Hankel, Toeplitz, and Vandermonde) whose entries are logarithmic coefficients for this class of functions are obtained. Some interesting consequences of these results are also highlighted, offering new findings within the class of functions with bounded turning.